Our house is on fire : scenes of a family and a planet in crisis - Thunberg, Greta, 2003-; Thunberg, Greta, 2003-; Thunberg, Svante, 1969-; Ernman, Malena; Ernman, Beata (Penguin Books, an imprint of Penguin Random House, 2020)
"When climate activist Greta Thunberg was eleven, her parents, Malena and Svante, and her little sister, Beata, were facing a crisis in their own home. Greta had stopped eating and speaking, and her mother and father had reconfigured their lives to care for her. Desperate and searching for answers, her parents discovered what was at the heart of Greta's distress: her imperiled future on a rapidly heating planet. Steered by Greta's determination to understand the truth and generate change, they began to see the deep connections between their own suffering and the planet's. Written by a remarkable family and told through the voice of an iconoclastic mother, Our House Is On Fire is the story of how they fought their problems at home by taking global action. And it is the story of how Greta decided to go on strike from school, igniting a worldwide rebellion." -- From back cover.